Can we reform capitalism for its own good? A roadmap to sustainability - Robert Guttmann (PSL Quarterly Review, 2023)
An intensifying combination of instability, inequality, and environmental degradation obliges us to consider how best to reform capitalism. The question of the system's reformability has deep historic roots in capitalism's long-wave dynamic where periods of crises have recurrently set in motion ambitious reform programs such as the New Deal in the 1930s or the Reagan/Thatcher Revolution in the 1980s. But there is nothing mechanical about this process. The same crisis dynamic also triggers destabilizing polarization in the body politic which hinders consensus for broad reform. And any such reform program must also address the transformational requirements of the moment. France's Régulation Theory (RT) can be quite helpful in this regard with its unique institutionalist approach to capitalism's historic evolution and its typology of crises. Using RT we identify the basic outlines of a progressive reform program rooted in sustainable development and global public goods.
Keywords: B51; E32; F55; P10; 330; reformability of capitalism; long waves; theory of régulation; sustainable development goals